Predictors of mortality in children with neuroblastoma - Rusida Harjayanti Sanindya Arum; Kristia Hermawan; Pudjo Hagung Widjajanto; Sutaryo Sutaryo (Paediatrica Indonesiana, 2023)
Background Neuroblastoma is an extracranial solid tumor originating from neural crest cells which failed to properly migrate. Neuroblastoma is commonly found in children under 12 months of age. The survival rate of these patients is still relatively low, both in developed countries and Indonesia. Objective To determine whether age, sex, primary tumor location, degree of cell differentiation, and patient compliance are associated with the survival of children with neuroblastoma at Dr.Sardjito Hospital. Methods This retrospective cohort study included pediatric neuroblastoma patients at Dr. Sardjito Hospital, Yogyakarta, Central Java, between January 2012 to September 2020, however there has been no evaluation about survival of neuroblastoma. We collected secondary data from medical records and registration data of pediatric cancer patients in the Pediatric Hematology Oncology Department of Dr. Sardjito Hospital, we matched te data based on medicals records and manual data in the ward and olyclinic, which included age at diagnosis, sex, primary tumor location, degree of cell differentiation, and patient adherence to therapy. To confirm weather the information about survived or death, apart from medical record we do tracking by telephone to the parent. Results we do the observation and calculating based on our retrospective data , Of 54 pediatric neuroblastoma patients, 54% were female. The median length of observation was 13.25 months, with an incidence rate of 62/100 person-years and a median survival of 13 months from the time of diagnosis. The 5-year survival rate in our study was 21.3%. Multivariate analysis revealed that stage IV patients had higher risk of death (HR 10.9; 95%CI 1.47 to 81.01; P=0.02) compared to other stages. Sub-group follow-up analysis revealed no significant difference in stage IV male patients compared to female patients (HR 1.62; 95%CI 0.81 to 3.22; P=0.172). The survivial in group with primary tumor location outside the adrenal medulla and stage IV was not significantly different from patients whose tumor location was unknown (HR 2.45; 95%CI 0.71 to 8.43; P=0.155). The group whose primary tumor location was in the adrenal medulla did not have a significant difference in survival compared to patients whose primary tumor location was unknown (HR 2.09; 95%CI 0.84 to 5.22; P=0.114). Conclusion The predictor factors studied are not significantly associated with mortality in children with neuroblastoma.